Cu-doped CeMnO2-supported Pt catalysts with high activity at industrial operating conditions for preferential CO oxidation in H2 - Jianlin Cao; Tao Xing; Zongzhuang Sun; Sheng Wei; Jiaqi Wang; Lexin Mao; Tao Liu; Zhi Li; Yongxiao Tuo; Xin Zhou; Hao Yan; Yibin Liu; et al. (Carbon Future)
Developing efficient, stable, and inexpensive catalysts for the preferential CO oxidation in H2 (CO-PROX) over a wide temperature range in the presence of CO2 and H2O is indispensable for the hydrogen purification process. Herein, CuO was introduced to the CeMnO2-supported Pt catalyst to modulate the oxygen activation capacity and provide the available number of active sites in CO-PROX. One part of the CuO species doped into CeO2 strongly interacts with Ce, thus enhancing the oxygen transfer capacity of the catalyst. The other part of CuO species located on the surface of the catalyst provides extra Cu+ sites available for low-temperature CO adsorption. This synergistic interaction with Pt sites further enhances CO and O2 activation, broadening the temperature window of high activity. The optimal Pt-10CuO/CeMnO2 catalyst exhibits complete CO conversion (CO/O2 ratio of 1:1) within the practical temperature range of 130–190 °C, even in the presence of CO2 and H2O, and remains stable at 150 °C for 76 h testing without any deactivation. This work will give a novel approach for the design of highly efficient inexpensive catalysts for industrial preferential oxidation of CO in H2, especially in the presence of CO2 and H2O.